Створення і впровадження провідних технологій ракетобудування під керівництвом Б.Є. Патона - Литвинов, А.П. (Питання історії науки і техніки, 2008)
Показан вклад директора института электросварки им. Е.О. Патона академика Б.Е. Патона в решение проблемы изготовления ракетно-космической техники. На протяжении 50-ти лет под его руководством и при участии были разработаны уникальные технологии сварки специальных сплавов для конструкций, работающих при сверхвысоких и при криогенных температурах. The paper describes the contribution of academician B.E.Paton, Director of the E.O.Paton Electric Welding Institute into solution of the problem of manufacturing aerospace systems. During 50 years unique technologies of welding special alloys for structures operating at super-high and cryogenic temperatures have been developed under his direction and with his participation.